Pediatric neurointervention: collimation on radiation exposure-associated lifetime excess tumor risk. (5th September 2016) - Chen, Karen; Paramasivam, Srinivasan; Berenstein, Alejandro
Abstract : Background: Intracranial vascular malformations in children are being addressed through a variety of treatment modalities including open surgery, external beam radiation, and image-guided neuroendovascular procedures. These patients often receive multiple treatments and incur serial exposures to ionizing radiation which has been linked to tumor development in population-based data. Objective: This study quantifies the effect of collimation on exposures from single procedures and over patient lifetimes to estimate excess risk of lifetime tumor development. Methods: 215 patients aged 0–21 years from a single center took part in the study. Radiation exposure from neuroendovascular procedures was tabulated and converted to brain doses using modeled data and extrapolated to risk ratios using results of population-based estimates found in the literature. Results: Lifetime and per procedure risk was highest in patients with brain arteriovenous malformations, brain arteriovenous fistulas, and vein of Galen malformations, a reflection of our institutional referral patterns. Across all pathologies the per procedure excess relative risk decreased from 13.4 to 2.3 when full collimation was employed. Lifetime excess relative risk decreased from 49.0 to 7.7 for full collimation. Conclusions: This is the first study to quantify the effect of collimation on lifetime and per procedure risk of tumor development in a pediatric population. In addition to collimation, technical and operator-based aspects of the neurointerventional suite are discussed to further reduce patient exposure without sacrificing image quality.